What is the impact of operations management on sustainable business growth? - Schwab, Leila; Gold, Stefan; Reiner, Gerald (My University, 2015)
The research aims at exploring how decisions made by managers of growing firms influence the growth trajectory of their firms and guide them towards sustainable business growth. For this end, during five consecutive years, we analyze all decisions made by a high-growth firm by means of a longitudinal case study of a Swiss family-owned wood construction company. We observe that firms can take advantage of their growth periods to improve their efficiency and responsibility towards stakeholders. The empirical analysis and theory development pave novel ways for research and business practice towards sustainable business growth.
, 2015
Keywords: Business growth management; Decision-making; Sustainability